2004
DOI: 10.1080/09546120412331290130
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ryan White and non-Ryan White funded HIV medical care facilities across four metropolitan areas: results from the antiretroviral treatment and access studies site survey

Abstract: The Ryan White Comprehensive AIDS Resources Emergency Act 1990 (CARE Act) is one of the largest federal programmes funding medical and support services for individuals with HIV disease. Data that report services and gaps in service coverage from the organizational perspective are very limited. The Antiretroviral Treatment and Access Studies included a mail survey of 176 HIV medical care facilities in four US inner cities on clinic characteristics, services and practices, and patient characteristics. Characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
2
6
0
Order By: Relevance
“…This is consistent with a study which found that 80% of Ryan White funded clinics, like ours, provide some type of risk reduction counseling (Valverde et al, 2004). However, as in previous studies (Marks et al, 2002;Morin et al, 2004;Myers et al, 2004), only a minority of patients reported discussing topics such as HIV status disclosure with providers.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a study which found that 80% of Ryan White funded clinics, like ours, provide some type of risk reduction counseling (Valverde et al, 2004). However, as in previous studies (Marks et al, 2002;Morin et al, 2004;Myers et al, 2004), only a minority of patients reported discussing topics such as HIV status disclosure with providers.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies support our findings related to the scope of services reported by KIs, such as a survey of 143 RWP and non-RWP funded HIV clinics (Valverde et al, 2004). After controlling for facility type and public versus private clinics, Valverde et al (2004) found that RWP clinics offered significantly more services for most measures, including extended hours, adherence support, risk-reduction counseling, and on-site support services such as nutrition counseling, medical and support service coordination, transportation assistance, and child care.…”
Section: Discussionsupporting
confidence: 90%
“…Primary care and mental health services were provided at each KI’s clinic in our study. Comparably, Valverde et al (2004) reported that 90% of RWP clinics provided primary care and that 74% offered mental health services. Sixty percent of KI clinics in our study had on-site pharmacies compared to 61% of RWP clinics in the Valverde et al (2004) study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations